2011
DOI: 10.3892/ijo.2011.1167
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin reduces tumor cell adhesion to human peritoneal mesothelial cells by decreased expression of VCAM-1 and β1 integrin

Abstract: Abstract. Peritoneal carcinomatosis describes cancer metastasis onto the surface of the peritoneum. It is frequently caused by ovarian and colorectal cancer. Once a tumor has penetrated the peritoneum, cancer cells disseminate into the abdominal cavity. Additionally, surgery can account for the spread of free tumor cells. Their subsequent adhesion to mesothelial cells (HMCs) initiates peritoneal carcinomatosis. Therefore, this study analyzed the effect of simvastatin on tumor cell adherence. HMCs were isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…SEM analysis reveals that the enhanced adhesion of tumour cells to mesenchymal MCs is not due to a mere exposure of underlying matrix but rather to an increased cell–cell interaction. The tumour cell–mesothelium interaction is mediated, at least in part, by β 1‐integrins , which could reflect that cancer cells bind to mesothelium‐associated ECM and/or to the MC adhesion molecule VCAM‐1 . In agreement with this notion, it has been described that cleavage of MC‐associated matrix proteins fibronectin and vitronectin by MMP‐2 enhances integrin‐mediated carcinoma–mesothelium attachment .…”
Section: Discussionmentioning
confidence: 74%
“…SEM analysis reveals that the enhanced adhesion of tumour cells to mesenchymal MCs is not due to a mere exposure of underlying matrix but rather to an increased cell–cell interaction. The tumour cell–mesothelium interaction is mediated, at least in part, by β 1‐integrins , which could reflect that cancer cells bind to mesothelium‐associated ECM and/or to the MC adhesion molecule VCAM‐1 . In agreement with this notion, it has been described that cleavage of MC‐associated matrix proteins fibronectin and vitronectin by MMP‐2 enhances integrin‐mediated carcinoma–mesothelium attachment .…”
Section: Discussionmentioning
confidence: 74%
“…Retrospective analysis of statin use in ovarian cancer [50, 51], endometrial cancer [51], gliomas [52], colorectal cancer [53], hepatocellular cancer [54], and prostate cancer [55] reveal reduced overall mortality, suggesting that statin therapy may have a protective effect against some cancers. Studies have shown that statins can affect multiple stages of ovarian cancer progression including: metastasis [56, 57], chemoresistance [58], and cytotoxicity [31, 32, 59, 60]. Treating ovarian cancer cells with statins and inhibitors of RhoA resulted in decreased cell dissemination in a NUDE mouse model of ovarian cancer [57].…”
Section: Discussionmentioning
confidence: 99%
“…Wagner et al analyzed the effect of simvastatin on colon cancer metastases to the peritoneum. Adhesion to mesothelial cells was significantly reduced by 10 µM simvastatin (P < 0.01) without any change in the expression of adhesion molecules [33].…”
Section: Cell Line Studiesmentioning
confidence: 92%